State of knowledge and perspectives on wild loquat: Uapaca kirkiana mell. Arg (Euphorbiaceae) in Malawi (Southern Africa) - Kokouvi Buno, Kokou; Ulemu, Msiska; Wouyo, Atakpama; Kimwanga Prosper, Salumu; Issa, Balde; Joyce, Nababi; Mavuto, Tembo; Paul, Munyenyembe (Revue Ecosystèmes et Paysages, 2024)
Various parts of the plant Uapaca kirkiana, Euphorbiaceae family, are widely used in African countries for medicinal, food, economic, and social purposes. In traditional African medicine, the plant is used to treat fever and infections. On a socio-economic level, the plant is recognized as contributing to the improvement of household income. Due to its socio-economic and therapeutic importance, it has become a plant widely used by populations and highly sought by researchers aiming at validating scientifically and/or supporting its traditional use and its adoption in domestication. Although it is widely used in traditional medicine and has socio-economic importance,there is a lack of information on its phytochemical composition and biological activityand socio-economic importance. Using searching tools such as Google Scholar, PubMed and library literature, a total of 1,235 articles were identified. To avoid duplication, articles indexed in multiple databases were removed, leaving 109 articles. Only 91 articles met the requirements and study inclusion criteria. Therefore, this review provides a systematic overview of the socio-economic importance, species structure, biological activities, phytochemical constituents, and ethnomedical properties of the plant. The data show that U. kirkiana is a promising plant with socio-economic and pharmacological potential and can therefore be useful in contributing to the fight against climate change and food security.